UPAYA PEMERINTAH CINA MENGATASI PERDAGANGAN OPIUM MELALUI PROGRAM SUBSTITUSI OPIUM DI MYANMAR UTARA TAHUN 2005-2010 - Ayu Krisnasari, Ni Wayan; Dharmiasih, D. A. Wiwik; Nugraha, A. A. Bagus Surya Widya (Program Studi Hubungan Internasional FISIP Universitas Udayana, 2017)
This qualitative research aims to describe the Chinese Government’s effort to resolve opium trafficking through the Opium Substitution Program in North Myanmar from 2005 to 2010. The author perceives the problem of opium trafficking on the border of China and Myanmar has influenced the Chinese Government to make an effort through the implementation of alternative development models which is applied to the opium substitution program. The opium substitution program is implemented through bilateral cooperation in Shan and Kachin areas of Northern Myanmar. The author finds that the opium substitution program is a sustainable long-term program with the aim of building local people's economy in the territory of North Myanmar that is adjusted to the social, cultural, and economic characteristics of local communities. Opium substitution program has been implemented by the Chinese Government through the provision of training and agricultural assistance for former opium farmers, as well as the implementation of agricultural investment schemes in North Myanmar. Key words: opium trafficking, bilateral cooperation, alternative development, opium substitution program.